Investigating Active Learning Model For Arabic Grammar Lectures - Hafidah, Hafidah; Isnaini, Rohmatun Lukluk; Kholis, Muhammad Nur (Ijaz Arabi Journal of Arabic Learning, 2024)
Arabic grammar learning is challenging and complex for learners to understand. This research aims to investigate lecturers and students learning Arabic grammar with an active learning model. This research uses a qualitative research method with an investigative approach. The data was obtained through interviews with four lecturers (Nahwu and Sharaf course teachers) and four students. It was then categorized, interpreted, and analyzed. The results showed that Arabic grammar learning already uses an active learning model. This is evidenced by the following five aspects: the application of student-centered learning, the use of engaging learning media, the creation of a pleasant environment, the use of problem-solving-based learning, and teamwork/collaboration in learning. The results of this study have an excellent opportunity to be adopted in Arabic language learning by all Islamic universities around Indonesia, especially in learning Nahwu and Sharaf.